Apoptosis is present in skeletal muscle of cachectic gastro-intestinal cancer patients - Busquets, Sílvia; Deans, Chris; Figueras, Maite; Moore-Carrasco, Rodrigo; López-Soriano, Francisco J.; Fearon, Kenneth C.H.; Argilés, Josep M. (Clinical nutrition (Edinburgh, Scotland), 2007)
Previous studies of our research group have shown that apoptosis is present in skeletal muscle of tumour-bearing animals subject to cachexia. For this reason we decided to investigate the apoptosis in skeletal muscle of cancer patients. In the present study, muscle biopsies from weight-losing patients with upper gastro-intestinal cancer showed a significant increase in muscle DNA fragmentation (three-fold), as compared with control subjects. The increase in DNA laddering was associated with an increase in poly(ADP-ribose) polymerase (PARP) cleavage (four-fold) as measured by western blotting. These two events indicate the presence of muscle apoptosis. These changes were associated with a decrease in MyoD protein content, suggesting important alterations in skeletal muscle physiology. The results presented therefore confirm that apoptosis is also present in human subjects undergoing cancer cachexia.